Whiskers - a unique strengthening materials - Mohammed Misbahul, Amin (National Institute of Science Communication and Information Resources, 2009)
Link to publisher's homepage at http://www.niscair.res.in/ScienceCommunication/Popularization%20of%20Science/scirep0.asp